2004
DOI: 10.1002/cne.20204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of limb exercise after spinal cord injury on motor neuron dendrite structure

Abstract: An integration center subserving locomotor leg movements resides in the upper lumbar spinal cord. If this neuronal network is preserved after a spinal cord injury, it is possible to stimulate this circuitry to initiate and promote walking. The several effective approaches (electrical stimulation, pharmacologic agents, physical therapy training programs) may all share a common modus operandi of altering synaptic activity within segmental spinal cord. To understand the neural substrate for the use-dependent beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 88 publications
4
90
1
2
Order By: Relevance
“…Given that the morphology of a motoneuron has a predominant effect on its electrophysiological properties, it is interesting that motoneuron structure is affected by training after spinal transection (Gazula et al, 2004). The size of the dendritic tree of motoneurons following spinal cord transection decreases, but these morphological features can be returned to normal values by training on a cycle.…”
Section: Neurophysiological Plasticity In Response To Trainingmentioning
confidence: 99%
“…Given that the morphology of a motoneuron has a predominant effect on its electrophysiological properties, it is interesting that motoneuron structure is affected by training after spinal transection (Gazula et al, 2004). The size of the dendritic tree of motoneurons following spinal cord transection decreases, but these morphological features can be returned to normal values by training on a cycle.…”
Section: Neurophysiological Plasticity In Response To Trainingmentioning
confidence: 99%
“…However, we cannot discount the possible alterations in the rest of the dendritic tree. Gazula et al (2004) found significant changes within the dendritic tree, including the number of primary dendrites 5 days after spinal cord transection in the rat. However, the spinal cord transection group that performed exercise was not different from the control group (no injury).…”
Section: Primary Dendritesmentioning
confidence: 86%
“…In addition, the use of artificial rearing ("pup in a cup" model) from postnatal days 4 to 14 has demonstrated altered contractile properties of the tongue retrusor musculature (Kinirons et al, 2003). The dendritic pattern, including the number of primary dendrites, is altered within 5 days of spinal cord transection in young rats (Gazula et al, 2004). However, the dendritic pattern is no different from a control group when the rats with spinal cord transection performed routine passive hindlimb exercise.…”
mentioning
confidence: 99%
“…In addition, neurons that do not ultimately die may undergo extensive morphological alterations including dendritic and somatic atrophy [13][14][15][16], as well as synaptic and dendritic remodeling [17]. By 1 week after thoracic spinal cord injury (SCI), neurons in the cord show atrophic dendritic arbors in addition to reduced soma size [18].…”
Section: Influence Of Injury On Dendritic Morphology and Structural Dmentioning
confidence: 99%